(untitled) (Journal of NELTA Gandaki, 2025)
The Journal of NELTA Gandaki (JoNG) stands as a notable forum in the fields of English language teaching (ELT), teacher education, and professional development. It provides ELT practitioners, both from Nepal and abroad, with an avenue to disseminate their research and pedagogical practices through academic writing. We are pleased to bring forth the eighth volume of JoNG, a one-star-rated JPPS, peer-reviewed open access journal indexed in NepJOL, published by the NELTA Gandaki Province Committee. This volume features a wide spectrum of empirical and theoretical contributions related to EFL pedagogy, the use of ICT and technology in ELT, as well as diverse aspects of the English language and literature. The first article conducts a critical analysis of the intricate relationship among language, identity, and emotion in Emily Brontë’s Wuthering Heights, investigating how Brontë’s linguistic choices inform character identities and emotional expressions, particularly within the frameworks of social class, gender, and psychological complexity. Similarly, the second article utilizes document analysis to examine the factors contributing to learner variability, which have led to diversity within ELT classes. Highlighting the issues of digital technology, the third article explores how digital tools influence languages, cultures, and social behaviours in Nepal. Following a descriptive research design, the fourth article investigates the multifaceted dimensions of the teaching-learning process, emphasizing the pivotal role of student-teacher rapport in enhancing educational productivity, analyzing the effects of English-only policies in Nepalese institutional schools on student-teacher dynamics, and incorporating teachers’ perspectives on this policy. Emphasizing the issue of assessment in higher education, the fifth article explores EFL teachers’ perceptions and practices of alternative assessment approaches in Nepal. Using the Google form survey, the sixth article examines the anxiety levels of secondary-level EFL students in Nepal as they acquire language skills in EFL classrooms. Similarly, focusing on teachers’ perceptions, practices, challenges and needs, the seventh article identifies strategies to enhance intercultural communicative competence (ICC) in classrooms defined by linguistic and cultural diversity. Likewise, the next article examines the disparity between the intended implementation of English medium instruction (EMI) and its actual practices across three secondary schools in Nepal. The ninth article critically examines the utilization of generative artificial intelligence (GenAI) and AI tools by Nepalese university educators in ELT, aiming to elucidate the impact of these technologies on teaching and learning outcomes, as well as the adaptations made by educators to their pedagogical practices for effective integration of these tools. Similarly, the next article investigates the challenges and practices associated with academic writing by reviewing existing online literature within both national and international contexts. Additionally, it explores the strategies employed by supervisors and research scholars to address these challenges effectively. Furthermore, in a narrative inquiry, the next article analyzes the strategies used by students for reading construction through reading English texts. Employing a phenomenological design, the final article explores perceptions of mobile-assisted English language learning (MAELL) in a Nepali university, focusing on the interplay of usage intensity and purpose, networked access, and behavioral nudges through the narratives of teachers and students. We envisage that this volume will serve as both an inspiration and a resource for educators and researchers in fostering a research-oriented academic culture. We express our sincere appreciation to the contributing authors, reviewers, and the entire NELTA community for their unwavering support and encouragement in making this issue possible. The JoNG remains committed to providing a scholarly platform for innovative ideas, exemplary pedagogical practices, and insightful research in the field of EFL. While the articles published herein are the property of NELTA Gandaki Province, the authors retain full responsibility for the accuracy of the content and for the perspectives expressed in their work. We warmly invite constructive feedback from our esteemed readers and well-wishers, which will contribute to the continuous enhancement of the quality and academic standards of the JoNG.